2019
DOI: 10.1002/casp.2421
|View full text |Cite
|
Sign up to set email alerts
|

Group efficacy as a moderator on the associations between perceived discrimination, acculturation orientations, and psychological well‐being

Abstract: We investigated whether associations between perceived discrimination (PD), acculturation orientations (desire for culture maintenance and desire for contact), and well‐being (psychological well‐being and life satisfaction) were moderated by group efficacy beliefs—the extent to which group members believe in their ability to achieve social change collectively. We recruited 163 Syrian refugees (Mage = 36.43, SD = 12.68; 88 females and 75 males) from a south‐eastern city in Turkey. PD was negatively associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
1
16
0
4
Order By: Relevance
“…However, Turkey is also the nation with the lowest value (among 38 countries) on the Migrant Integration Policy Index (Huddleston, Bilgili, Joki, & Vankova, 2015), which measures the degree to which a given country endorses integration policies across multiple policy areas (i.e., labor market mobility, family reunion, education, health, political participation, permanent residence, access to formal citizenship, and anti‐discrimination policies). Recent studies with Syrian refugees in Turkey have indicated that experiencing ethnic discrimination is negatively related to maintaining one's Syrian cultural heritage, and is positively linked to adopting the destination (Turkish) culture among refugee adults (Bagci & Canpolat, 2020). In addition, Çelebi, Verkuyten, and Bagci (2017) found that high perceived ethnic discrimination is associated with poor physical and mental health among refugee adults who do not experience a sense of control, distinctiveness, and meaningfulness derived from their ethnic identity.…”
Section: Introductionmentioning
confidence: 99%
“…However, Turkey is also the nation with the lowest value (among 38 countries) on the Migrant Integration Policy Index (Huddleston, Bilgili, Joki, & Vankova, 2015), which measures the degree to which a given country endorses integration policies across multiple policy areas (i.e., labor market mobility, family reunion, education, health, political participation, permanent residence, access to formal citizenship, and anti‐discrimination policies). Recent studies with Syrian refugees in Turkey have indicated that experiencing ethnic discrimination is negatively related to maintaining one's Syrian cultural heritage, and is positively linked to adopting the destination (Turkish) culture among refugee adults (Bagci & Canpolat, 2020). In addition, Çelebi, Verkuyten, and Bagci (2017) found that high perceived ethnic discrimination is associated with poor physical and mental health among refugee adults who do not experience a sense of control, distinctiveness, and meaningfulness derived from their ethnic identity.…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, there are reports on the mediating role of personality traits [ 42 ], ethnic affirmation [ 43 ], atheist identification [ 44 ], or sense of control [ 45 ]. In the immigrant population, there are reports of both moderating factors such as group efficacy [ 46 ], group membership [ 47 ] and identity [ 48 , 49 ], as well as mediating factors such as self-esteem [ 50 ], affect [ 51 ], employability [ 52 ], and group identity [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2017) reported that higher levels of perceived discrimination are related to lower levels of mental and physical health among refugees, but not for those refugees who experience a sense of efficacy from their ethnic identity. Moreover, Bagci and Canpolat (2020) found that, among adult refugees in Turkey, perceived discrimination is negatively associated with the maintenance of Syrian culture and it is positively associated with adopting Turkish culture. Specifically, recent studies with refugee adolescents in Turkey found that psychosocial resilience is associated with a high level of hope, perceived social support from family, quantity of social contact, and sense of school belonging (Bozdağ, 2020; Sarıpınar, 2019).…”
Section: Study IImentioning
confidence: 99%